1986
DOI: 10.1111/j.1745-6606.1986.tb00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Search for Nutrition Information: A Probit Analysis of the Use of Different Information Sources

Abstract: Two general approaches have been taken to examine consumers' search for and use of information about food and nutrition. The first approach, adopted largely by consumer researchers, has focused on the extent, methods, and strategies of prepurchase informationseeking (Jacoby, Chestnut, and Silberman 1977;McCullough and Best 1980;Moore and Lehmann 1980). The other research approach, used largely by nutrition education researchers, has focused on intervention programs. This work has examined the diet and knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 32 publications
1
37
0
1
Order By: Relevance
“…There is much debate on how the amount and type of product information on a label might influence nutritional beliefs and purchase patterns (Bender and Derby, 1992). Some researchers have empirically shown that a miscomprehended nutrition label or one containing too much information can decrease the accuracy of oneÕs judgments about products (Feick et al, 1986;Byrdbredbenner, 1994). Other researchers argue that more information can instead lead to better understanding and willingness to purchase the product (Lepkowska-White and Parsons, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…There is much debate on how the amount and type of product information on a label might influence nutritional beliefs and purchase patterns (Bender and Derby, 1992). Some researchers have empirically shown that a miscomprehended nutrition label or one containing too much information can decrease the accuracy of oneÕs judgments about products (Feick et al, 1986;Byrdbredbenner, 1994). Other researchers argue that more information can instead lead to better understanding and willingness to purchase the product (Lepkowska-White and Parsons, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…flavonoid, Omega-3). On a more general level, Feick, Herrmann, and Warland (1986) find that consumers who cared about their nutrition searched for more information about health-related claims. Related to this issue, Moorman and Matulich (1993) show that consumers with higher health motivation are more likely to engage in healthattitudes tow functional foods and purchase behaviour.…”
Section: Educationmentioning
confidence: 99%
“…Evidence suggested that informational interpersonal influences could affect consumer decision processes regarding product evaluations [60], product selections [27], and purchase decisions [62]. Thus, it is highly likely that in the green context, green consumers are relying green experts or opinion leaders' information to purchase green products.…”
Section: The Positive Effect Of Informational Interpersonal Influencementioning
confidence: 99%
“…From the theory of innovation diffusion perspective, Flynn et al (1996) suggested that opinion seeking satisfies the need that to improve the product choice and to reduce perceived risk [52]. Feick et al (1986) mentioned that opinion seekers collect information or opinions from interpersonal sources in order to evaluate products and make purchase decisions [60]. Consumers' main concern is to make the right choice from a variety of product or brand evaluations.…”
Section: The Positive Effect Of Informational Interpersonal Influencementioning
confidence: 99%